Demystifying Horizontal/Vertical Cultural Difference in Green Consumption: A Cross-Cultural Comparative Study. Issue 5 (7th October 2021) - Rahman, Saleem ur; Luomala, Harri
Abstract: To understand green consumption in cross-cultural context, this study examines the influence of horizontal individualism (HI-Finnish) and vertical collectivism (VC-Pakistani) cultural values on consumers' attitude toward green products and purchase intentions. Besides, the mediating role of environmental responsibility is examined for the relationship between these cultural values and consumers' attitude toward green products. Partial Least Square structural equation modeling (PLS-SEM) analysis are performed to measure the significance of the hypothesized model and to assess differences between these two countries. This study empirically validates that these cultural variations can determine green consumption by consumers in each country. The results show an insignificant influence of horizontal individualism and vertical collectivism cultural values on consumers' attitude toward green products, but a positive influence on environmental responsibility. The impact of environmental responsibility on consumers' attitude toward green products and of their attitude toward green products on purchase intention was also positive. Environmental responsibility plays the role of a full mediator between cultural values and consumers' attitude toward green products. The findings of this study may help practitioners in the development of culturally appropriate green marketing and advertising strategies.